2007
DOI: 10.1126/science.1142365
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Synthesis and Synaptic Insertion of GluR2 for mGluR-LTD in the Ventral Tegmental Area

Abstract: The activation of metabotropic glutamate receptors (mGluRs) leads to long-term depression (mGluR-LTD) at many synapses of the brain. The induction of mGluR-LTD is well characterized, whereas the mechanisms underlying its expression remain largely elusive. mGluR-LTD in the ventral tegmental area (VTA) efficiently reverses cocaine-induced strengthening of excitatory inputs onto dopamine neurons. We show that mGluR-LTD is expressed by an exchange of GluR2-lacking AMPA receptors for GluR2-containing receptors with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
272
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(286 citation statements)
references
References 25 publications
13
272
0
1
Order By: Relevance
“…For example, an important recent study identified a role for mTORC1 in alcohol-cue memory reconsolidation (Barak et al, 2013). Further, intra-amygdala or hippocampal rapamycin suppresses the consolidation and reconsolidation of fear memories (Blundell et al, 2008;Parsons et al, 2006) and mTORC1 is required for cocaine-induced plasticity in VTA dopamine neurons (Mameli et al, 2007).…”
Section: Inhibition Of Mtorc1 In the Nacsh Reduces Drugseeking Behavimentioning
confidence: 99%
See 3 more Smart Citations
“…For example, an important recent study identified a role for mTORC1 in alcohol-cue memory reconsolidation (Barak et al, 2013). Further, intra-amygdala or hippocampal rapamycin suppresses the consolidation and reconsolidation of fear memories (Blundell et al, 2008;Parsons et al, 2006) and mTORC1 is required for cocaine-induced plasticity in VTA dopamine neurons (Mameli et al, 2007).…”
Section: Inhibition Of Mtorc1 In the Nacsh Reduces Drugseeking Behavimentioning
confidence: 99%
“…Cocaine seeking has been shown to require an increase in translation, trafficking, and signaling through GluA1 AMPARs in the NAC, and CAMKIIa has a well-established role in this process (Anderson et al, 2008;Conrad et al, 2008;Ferrario et al, 2011;Lisman et al, 2012;Opazo et al, 2010). Given the functional link between these glutamate signaling molecules and reinstatement, the protective effects of intra-NACsh rapamycin on drug seeking might be mediated by a disruption in withdrawal-induced increases in synaptic GluA1s that increase the propensity for drug seeking (Anderson et al, 2008;Conrad et al, 2008;Mameli et al, 2007;Wolf, 2010). An important additional consideration is the possibility that rapamycin treatment disrupted associative memory processes during the drug-taking phase.…”
Section: Inhibition Of Mtorc1 In the Nacsh Reduces Drugseeking Behavimentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, S6K and 4E-BP are localized at the synapse (6,13,14), where mTORC1 was shown to be important for stabilizing plastic changes (15,16). The mTORC1-mediated pathway was also reported to control soma and dendritic morphology (17), long-term potentiation, and long-term depression (6,18). Accordingly, the mTORC1-mediated signaling pathway has been shown to contribute to memory formation, consolidation, and reconsolidation (6,19), as well as memory deficits (20).…”
mentioning
confidence: 99%